2014
DOI: 10.1038/cr.2014.71
|View full text |Cite
|
Sign up to set email alerts
|

An epigenomic approach to therapy for tamoxifen-resistant breast cancer

Abstract: Tamoxifen has been a frontline treatment for estrogen receptor alpha (ERα)-positive breast tumors in premenopausal women. However, resistance to tamoxifen occurs in many patients. ER still plays a critical role in the growth of breast cancer cells with acquired tamoxifen resistance, suggesting that ERα remains a valid target for treatment of tamoxifen-resistant (Tam-R) breast cancer. In an effort to identify novel regulators of ERα signaling, through a small-scale siRNA screen against histone methyl modifiers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
169
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(182 citation statements)
references
References 40 publications
(42 reference statements)
11
169
1
1
Order By: Relevance
“…The fact that the elevated function of each of the NSD2 target genes is required for NSD2-mediated therapeutic resistance emphasizes the importance of the coordinated nature of NSD2 function in metabolic reprogramming. Recently, NSD2 was implicated in regulation of ERα gene expression [19]. Consistent with this, we also found that NSD2 knockdown decreased ERα expression in tamoxifensensitive breast cancer cells.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The fact that the elevated function of each of the NSD2 target genes is required for NSD2-mediated therapeutic resistance emphasizes the importance of the coordinated nature of NSD2 function in metabolic reprogramming. Recently, NSD2 was implicated in regulation of ERα gene expression [19]. Consistent with this, we also found that NSD2 knockdown decreased ERα expression in tamoxifensensitive breast cancer cells.…”
Section: Discussionsupporting
confidence: 77%
“…NSD2 can also act as a coactivator of NF-κB in mediating cytokinedependent autocrine loop for cancer cell growth and survival [15]. One recent study showed that NSD2 could directly regulate estrogen receptor ERα expression in breast cancer cells [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although molecular typing and screening in recent years have provided an effective method for choosing the most sensitive candidates for endocrine therapy, a considerable number of patients exist that are not sensitive to endocrine therapy (17,18). Therefore, further investigation of the specific indicators is necessary for improving the efficacy of endocrine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Комбинация эндокринотерапии и блокаторов факторов роста может быть полезной стратегией для пре-одоления резистентности к эндокринотерапии [75] Определение Ki-67…”
Section: внутренние подтипыunclassified